Abatacept (CTLA‐4IG) treatment reduces the migratory capacity of monocytes in patients with rheumatoid arthritis. Issue 3 (25th February 2013) - Bonelli, M.; Ferner, E.; Göschl, L.; Blüml, S.; Hladik, A.; Karonitsch, T.; Kiener, H. P.; Byrne, R.; Niederreiter, B.; Steiner, C. W.; Rath, E.; Bergmann, M.; et al.
Abstract Objective The binding of abatacept (CTLA‐4Ig) to the B7 ligands CD80 and CD86 prevents the engagement of CD28 on T cells and thereby prevents effector T cell activation. In addition, a direct effect of CTLA‐4Ig on antigen‐presenting cells (APCs) could contribute to the therapeutic effect. To further elucidate the mechanism of CTLA‐4Ig, we performed phenotype and functional analyses of APCs in patients with rheumatoid arthritis (RA) before and after the initiation of CTLA‐4Ig therapy. Methods Peripheral blood mononuclear cells were analyzed before and at 2 and 4 weeks after the initiation of CTLA‐4Ig therapy. Proportions of APCs were determined by flow cytometry. CD14+ monocytes were further analyzed for the expression of costimulatory and adhesion molecules and for their transendothelial migratory capacity in vitro. In addition, CD14+ monocytes from healthy controls were analyzed for their migratory and spreading capacity. Results Proportions and absolute numbers of monocytes were significantly increased in RA patients treated with CTLA‐4Ig. The expression of several adhesion molecules was significantly diminished. In addition, monocytes displayed a significant reduction in their endothelial adhesion and transendothelial migratory capacity upon treatment with CTLA‐4Ig. Likewise, isolated monocytes from healthy controls revealed a significant reduction in their migratory and spreading activity after preincubation with CTLA‐4Ig or anti‐CD80 and anti‐CD86 antibodies. Conclusion We describe direct effects of CTLA‐4Ig therapy on phenotype and functional characteristics of monocytes in RA patients that might interfere with the migration of monocytes to the synovial tissue. This additional mechanism of CTLA‐4Ig might contribute to the beneficial effects of CTLA‐4Ig treatment in RA patients.